ФИЗКУЛЬТУРНО-СПОРТИВНАЯ ДЕЯТЕЛЬНОСТЬ – КАК БАЗОВЫЙ ФАКТОР ФИЗИЧЕСКОЙ ПОДГОТОВЛЕННОСТИ СТУДЕНЧЕСКОЙ МОЛОДЁЖИ - Юсупов, Г.А. (SCIENCE and SOCIETY, 2020)
Based on the questionnaire, the article analyzes the attitude of students to physical education and the importance of physical education classes to maintain and strengthen health. The level of physical fitness and the functional state of students studying in non-sports faculties of universities has been assessed. Low physical fitness for a number of physical qualities and physical performance has been established.